A Review on Solar Based Wireless EV Charging System - Prof. Shital Ganorkar,; Alisha Meshram,; Yash Kumbhalkar,; Sachinkumar Neware,; Damini Chandankhele, (International Journal of Scientific Research in Science and Technology, 2025)
In our rapidly declining environment, the need for electric vehicles (EVs) has become essential. The Indian government aims to transition to exclusively electric vehicles by 2030. However, a significant barrier to widespread EV adoption is the lengthy charging time, necessitating the development of fast-charging solutions and robust charging infrastructure. An adequate charging network is crucial for this transition. With the increasing use of EVs, the current power supply could face significant instability. The "solar-based wireless EV charger" technique addresses this challenges by utilizing renewable energy technology. In this system, solar energy is converted into electrical energy and stored in a lead-acid battery. A battery management unit then facilitates a wireless charging system, allowing the stored energy to be used for charging electric vehicles.
Keywords: Solar panel; BMS; Wireless Charging coil; ESP8266; IOT Monitoring; Relay Module